Fatores maternos e neonatais associados ao aleitamento materno em recém-nascidos pré-termos em acompanhamento no aplicativo Universo Prematuro® - Lima, Natália Mirelle Amaral de (2021)
Introduction: Breast milk is the ideal food for child growth and development, especially in premature newborns, being one of the most sensitive measures of health promotion. Objective: To identify and correlate maternal and infant factors to breastfeeding in preterm newborns assisted in a Child Friendly Hospital, during hospital discharge, of a group selected for follow-up at home. Methodological procedure: Analytical study, observational and cross-sectional study with 46 premature infants admitted to an Intermediate Care Unit I and II and their respective mothers. The premature infants were prescribed for hospital discharge and were inserted in the Premature Universe application. The first stage of the research that was addressed in this study, included the application of forms for maternal and child evaluation applied to the mother and/or guardian and the collection of information through the records in the child's records at hospital discharge. The later stages of the research addressed the prevalence of breastfeeding at home and its benefits for the sample group in the Premature Universe application. The absolute and relative frequencies between the independent variables and breastfeeding were determined and compared. Afterwards, the linear and logistic regression tests were applied to determine the beta coefficient and odds ratio, respectively. The degree of significance considered was 0.05. The statistical analyses were performed with the help of the SPSS program. Results: The prevalence of exclusive breastfeeding among preterm infants was 23.6% at hospital discharge, with a predominance of mixed breastfeeding in 56.5% of the sample. The main feeding route was through the orogastric tube, in 59.57%, and only four (8.7%) exclusively breastfed. The factors associated with exclusive breastfeeding/mixed were primigestation (p<0.001), no alcohol consumption (p (p<0.043), desire for pregnancy (p<0.014), ower number of previous deliveries (p<0.001) and offering the breast to the child in some period of hospitalization (p<0.001). The consumption of exclusive breast milk was associated with maternal schooling (p<0.022), a lower amount of children with weight gain (p<0.046) and breastfeeding in the first hours (p<0.05). The number of consultations, receipt of prenatal information, type of delivery, Apgar Score, duration of the child's hospitalization were not associated. Mothers who manifested a desire for pregnancy, who did not use alcohol/smoking during pregnancy, who breastfed their children in the first hours of life and who offered breastfeeding at some point of hospitalization (p<0.05), had more chances to breastfeed. Mothers of children who received breast milk during hospitalization had less previous deliveries and lost more weight (p<0.001). The children were born with higher gestational age (p<0.001), heavier weight (p<0.001), higher score of Apgar Score in the first minute (p<0.045) and remained hospitalized for a shorter period (p<0.001). Final considerations: There was a low prevalence of breastfeeding exclusive to premature infants at hospital discharge, which reinforces the urgency of reviewing the strategies already implemented and of new breastfeeding interventions that promote, support and protect adequate feeding with home follow-up. Keywords: Breastfeeeding. Infant,premature. Weaning.